Relative cost-effectiveness of long-acting injectable cabotegravir versus oral pre-exposure prophylaxis in South Africa based on the HPTN 083 and HPTN 084 trials: a modelled economic evaluation and threshold analysis. Issue 12 (December 2022) - Jamieson, Lise; Johnson, Leigh F; Nichols, Brooke E; Delany-Moretlwe, Sinead; Hosseinipour, Mina C; Russell, Colin; Meyer-Rath, Gesine
Summary: Background: Long-acting injectable cabotegravir, a drug taken every 2 months, has been shown to be more effective at preventing HIV infection than daily oral tenofovir disoproxil fumarate and emtricitabine, but its cost-effectiveness in a high-prevalence setting is not known. We aimed to estimate the incremental cost-effectiveness of long-acting injectable cabotegravir compared with tenofovir disoproxil fumarate and emtricitabine in South Africa, using methods standard to government planning, and to determine the threshold price at which long-acting injectable cabotegravir is as cost-effective as tenofovir disoproxil fumarate and emtricitabine. Methods: In this modelled economic evaluation and threshold analysis, we updated a deterministic model of the South African HIV epidemic with data from the HPTN 083 and HPTN 084 trials to evaluate the effect of tenofovir disoproxil fumarate and emtricitabine and long-acting injectable cabotegravir provision to heterosexual adolescents and young women and men aged 15–24 years, female sex workers, and men who have sex with men. We estimated the average intervention cost, in 2021 US$, using ingredients-based costing, and modelled the cost-effectiveness of two coverage scenarios (medium or high, assuming higher uptake of long-acting injectable cabotegravir than tenofovir disoproxil fumarate and emtricitabine throughout) and, for long-acting injectable cabotegravir, two duration subscenarios (minimum: same pre-exposure prophylaxis duration as for tenofovir disoproxil fumarate and emtricitabine; maximum: longer duration than tenofovir disoproxil fumarate and emtricitabine) over 2022–41. Findings: Across long-acting injectable cabotegravir scenarios, 15–28% more new HIV infections were averted compared with the baseline scenario (current tenofovir disoproxil fumarate and emtricitabine roll-out). In scenarios with increased coverage with oral tenofovir disoproxil fumarate and emtricitabine, 4–8% more new HIV infections were averted compared with the baseline scenario. If long-acting injectable cabotegravir drug costs were equal to those of tenofovir disoproxil fumarate and emtricitabine for the same 2-month period, the incremental cost of long-acting injectable cabotegravir to the HIV programme was higher than that of tenofovir disoproxil fumarate and emtricitabine (5–10% vs 2–4%) due to higher assumed uptake of long-acting injectable cabotegravir. The cost per infection averted was $6053–6610 (tenofovir disoproxil fumarate and emtricitabine) and $4471–6785 (long-acting injectable cabotegravir). The cost per long-acting cabotegravir injection needed to be less than twice that of a 2-month supply of tenofovir disoproxil fumarate and emtricitabine to remain as cost-effective, with threshold prices ranging between $9·03 per injection (high coverage; maximum duration) and $14·47 per injection (medium coverage; minimum duration). Interpretation: Long-acting injectable cabotegravir could potentially substantially change HIV prevention. However, for its implementation to be financially feasible across low-income and middle-income countries with high HIV incidence, long-acting injectable cabotegravir must be reasonably priced. Funding: United States Agency for International Development, The Bill & Melinda Gates Foundation.